2020
DOI: 10.2147/cia.s250629
|View full text |Cite
|
Sign up to set email alerts
|

<p>Trunk Skeletal Muscle Mass and Phase Angle Measured by Bioelectrical Impedance Analysis are Associated with the Chance of Femoral Neck Fracture in Very Elderly People</p>

Abstract: Background: The study aimed to investigate the potential association of trunk skeletal muscle mass (tSM) and phase angle measured by bioelectrical impedance analysis (BIA) with the chance of femoral neck fractures in very elderly people. Patients and Methods: This case-control study enrolled 78 femoral neck fracture patients aged over 75 years (29 males) and 1:2 matched healthy controls. All participants were subjected to BIA examination by specialists. tSM, the corrected values by height squared of tSM (tSMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…Previous studies have reported that PhA in patients with hip fractures was signi cantly lower than in healthy older adults 27 , and in this study, patients who developed sarcopenia after hip fracture surgery showed lower PhA and higher ECW/TBW than patients without sarcopenia. ECW/TBW is the ratio of extracellular uid to body water content and is elevated in edema-causing diseases such as dialysis and heart failure 28 .…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have reported that PhA in patients with hip fractures was signi cantly lower than in healthy older adults 27 , and in this study, patients who developed sarcopenia after hip fracture surgery showed lower PhA and higher ECW/TBW than patients without sarcopenia. ECW/TBW is the ratio of extracellular uid to body water content and is elevated in edema-causing diseases such as dialysis and heart failure 28 .…”
Section: Discussionsupporting
confidence: 60%
“…11,32 Many BIA indicators including segmental skeletal muscle, body fat and water content provide useful supportive information to facilitate clinical diagnosis. 33,34 Here, we measured body composition indicators including skeletal muscle mass using BIA with the aim of more accurate characterization of the link between sarcopenia and AML. MAMC measured by BIA can reflect muscle mass and performance and has been used as an indicator of nutritional status.…”
mentioning
confidence: 99%
“… 8 ) BIA is especially useful for site-specific evaluation of appendicular and trunk muscle mass. 9 , 10 ) Previous studies investigating muscle mass using the BIA method reported decreased appendicular muscle mass (AMM) in about 60% of patients with hip fracture. 11 ) It has been reported that decreased AMM is associated with a decline in physical function 12 ) and that a decrease in AMM as evaluated by BIA is associated with decreased ADL and increased mortality.…”
Section: Introductionmentioning
confidence: 99%